Estimating the monetary cost of biological invasions to South Africa - Emily J. McCulloch-Jones; Ross N. Cuthbert; Brian W. van Wilgen; John R. U. Wilson (Biological Invasions, 2024)
Estimates of the cost of damage caused by invasive alien speices and the money spent addressing biological invasions are needed to guide policy and management. Here, we quantify the known monetary costs of biological invasions to South Africa, using data from the InvaCost database, literature searches, and stakeholders. The Department of Forestry, Fisheries and the Environment, and agencies directly funded by them, provided most of the information on money spent, with very little information was available from other government agencies and the private sector. There was also very little information on the monetary costs due to the impacts of invasions. Between 1960 and 2023, ZAR9.6 billion (adjusted to 2022 values) was spent managing biological invasions in South Africa. This is only 4% of the money predicted as being necessary for management, which amounted to ZAR231.8 billion in 2022 values. There is uncertainty in the obtained estimates due to a paucity of information on both impacts and management costs. A few key points emerged from our analysis: the cost of damage caused by invasions far exceeds expenditure on control; the amount spent on control is much less than what is predicted to be needed; almost all management has focussed on a few invasive plant species; and there are large gaps in information that reduce the confidence in our estimates. Transparent cost reporting, strategic public–private collaborations, standardised impact metrics, and reliable assessments of management effectiveness are needed to enable South Africa to more effectively account for and prioritise investments.